Comparison of Tubeless Mini Percutaneous Nephrolithotomy and With Tubed Mini Percutaneous Nephrolithotomy for Kidney Stones: A Prospective Study - Shah, Ram Sagar; Mishra, Kartikesh; Sah, Sachidanand; Karn, Prakash; Thapa, Niraj (Journal of Nepalgunj Medical College, 2024)
Introduction: Renal stone disease is a prevalent condition with a high recurrence rate, significantly impacting patients’ quality of life. Different modalities of renal surgery are using globally. Mini Percutaneous nephrolithotomy (PCNL) is an effective treatment for renal stones. Due to the significant pain and morbidity after Percutaneous nephrolithotomy because of nephrostomy tubes, various modifications of Percutaneous nephrolithotomy are being performed. Aims: To compare the safety and efficacy of tubeless mini Percutaneous nephrolithotomy against tubed mini Percutaneous nephrolithotomy. Methods: It is prospective Hospital study conducted from July 2021 to December 2022 at Nobel Medical College. total 100 patients under inclusion criteria were divided into two groups: 50 in Group A (tubed mini Percutaneous nephrolithotomy) and 50 in Group B (tubeless mini Percutaneous nephrolithotomy) alternatively. The 2 groups were compared for Clavien Dindo grading of complications in Percutaneous nephrolithotomy analgesic requirements, hospital stay and time of operative procedure. Data was analysed by using the chi-square test for qualitative variables and the student t test for quantitative variables. A P value 0.05 was considered significant. Ethical clearance was obtained from institutional review committee. Results: The mean age was similar between groups (Group A: 35.44 years; Group B: 36.26 years). Complications were comparable, with postoperative pyrexia being the most common in both groups. However, Group B demonstrated significantly shorter hospital stays (80% discharged within 2 days vs. 30% in Group A) and lower analgesic requirements (p < 0.05). Conclusion: Tubeless mini Percutaneous nephrolithotomy is a safe and effective alternative for selected patients, offering reduced hospital stays and lower analgesic needs compared to tubed mini Percutaneous nephrolithotomy.